School Absenteeism: the Interpretation of Teacher’s Reports - Dereškevičius, Pranas (Acta Paedagogica Vilnensia, 2001)
The purpose of the article is to show that truancy and school absenteeism are complex multidimensional problem and that teachers and researchers need to understand the issues involved in these phenomena. The distribution of dropouts based on the data produced on teacher’s reports about 392 truants and 108 absentees from comprehensive schools prove, that persistent absenteeism does increase substantially in the later years of schooling. Dropping from schools is a progressing phenomenon, reaching a peak at the age of 13-15 in the eight, seventh and sixth grades. Two thirds of dropouts had already had failures in previous years. That date shows that over one third of dropouts started schooling before the age of seven. That reasons for pupil non - attendance are generally well known, indeed, they have not changed. This paper considers some of the reasons for pupils missing school and examines how recent research (by D. Beresnevičienė, V Rimkevičienė and V Targamadzė) has added new dimensions to the topic, while pointing out that this work has failed to reduce or overcome the phenomenon.